As múltiplas linguagens e o desenvolvimento integral das crianças no cotidiano de uma escola pública de educação infantil no município de Parintins-AM - Azevedo, Sâmia Mendes de (Brasil, 2023)
This research with a qualitative approach has the general objective of investigating how multiple languages contribute to the integral development of children and how these expressive manifestations are present in the daily life of Early Childhood Education. The study is characterized as bibliographic research and field research. The field research was carried out in a Children's Educational Center (CEI) of the public school network in the urban area of the municipality of Parintins-AM. The participating subjects are two teachers and children from two preschool classes. The instruments and techniques used for data collection were: participant observation of teaching practices, analysis of teaching plans and pedagogical activities with records in the field diary. The results obtained reveal that multiple languages play an important role in the integral development of the child, manifesting themselves in early childhood education through verbal language, dance, music, reading images, theater, cinema, gestures, free drawing and painting. However, there is predominance in the pedagogical practices of languages related to writing and speaking, as well as in the weekly didactic plans elaborated by the teachers. With this, it is concluded that the different languages need to be equally potentiated in the daily life of preschool, so that children can express themselves considering the different expressive forms of childhood. Therefore, it is necessary to expand the immersion of children in the universe of languages through the Fields of experiences and materials so that they can expand their universe of knowledge, their imagination and way of communicating and interacting with the world and with others.